The relevance of the value-relevance literature for financial accounting standard setting - Holthausen, Robert W.; Watts, Ross L. (Journal of Accounting and Economics, 2001)
In this paper we critically evaluate the standard-setting inferences that can be drawn from value relevance research studies that are motivated by standard setting. Our evaluation concentrates on the theories of accounting, standard setting and valuation that underlie those inferences. Unless those underlying theories are descriptive of accounting, standard setting and valuation, the value-relevance literature's reported associations between accounting numbers and common equity valuations have limited implications or inferences for standard setting; they are mere associations. We argue that the underlying theories are not descriptive and hence drawing standard-setting inferences is difficult.